Patients' views on an education booklet following spinal surgery - McGregor,AH; Henley,A; Morris,TP; Dore,CJ (European Spine Journal, 2012)
Purpose This study evaluated an evidence-based educationbooklet developed for patients undergoing spinal surgerywhich was used as a treatment intervention in a multi-centre,factorial, randomised controlled trial (FASTER: Functionafter spinal treatment, exercise and rehabilitation) investigatingthe post-operative management of spinal surgerypatients. This study sought to determine the acceptability andcontent of the booklet to patients.Methods Patients receiving the educational bookletbefore discharge from hospital as part of the FASTERstudy were asked to complete an evaluation, which ratedthe booklet ‘‘Your Back Operation’’ with regard to content,information, usability, etc. using forced and open questions.This assessment was conducted at the same time asthe initial 6-week post-operative review performed as partof the larger study.Results Therefore, 97% of the 117 trial participants whoreturned their 6-week evaluation and randomised to receivea booklet returned their questionnaire. The booklet washighly rated receiving an overall rating of 7 or more out of10 from 101/111 (91%), and high ratings for content,readability and information. The booklet’s key messageswere clear to the majority of patients; however, manypatients highlighted deficiencies with respect to contentparticularly in relation to wound care and exercise.Conclusions Patients valued the booklet and rated itscontent highly. Many suggested that the booklet bedeveloped further and there was a clear desire for specificexercises to be included even though there is no evidenceto support specific exercise prescription.